MATHEMATICAL MODELLING OF BRICK WALLS: A GEOMETRY LEARNING CONTEXT - Nasrum, Akbar; Hidayati, Ully (JME (Journal of Mathematics Education), 2025)
Mathematics learning at the junior secondary school level continues to face challenges related to the limited connection between mathematical concepts and students’ real-life experiences, particularly in geometry and measurement topics. This study aims to explore mathematical concepts embedded in the construction of subsidized house walls and to model the calculation of material volume and cost estimation as a real-world context for mathematics learning at the junior secondary school level. A qualitative descriptive approach with an exploratory design was employed. The object of the study was a subsidized house located in the Citra Latambaga Housing Complex, Latambaga District, Kolaka Regency, with a standardized building size of 6 m × 6 m and uniform room layouts. Data were collected through observation, measurement, and documentation, and analyzed using simple mathematical modeling aligned with the junior secondary school mathematics curriculum. The findings indicate that wall construction activities involve mathematical concepts such as the volume of rectangular prisms, unit conversion, ratio, estimation, and material cost calculation. The cost estimation results reveal significant differences between the use of red bricks and lightweight concrete blocks for the same wall volume, providing opportunities to introduce simple optimization problems in junior secondary school mathematics learning. This study concludes that the construction of subsidized house walls constitutes an authentic and meaningful context for teaching geometry and mathematical modeling, thereby supporting more contextualized and relevant mathematics learning at the junior secondary school level.